The socio-cultural conditioning of modern educational transformation - Стежко, З.В.; Стежко, Г.П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
A theoretical analysis of the role of philosophy of education in the formation of reflective thinking, tolerance personality defined methods and psycho-pedagogical conditions of the educational process school day postmodern.